2011
DOI: 10.1364/oe.19.003627
|View full text |Cite
|
Sign up to set email alerts
|

Design of high-transmission metallic meander stacks with different grating periodicities for subwavelength-imaging applications

Abstract: When replacing a bulk negative index material (NIM) with two resonant surfaces that allow for surface plasmon polariton (SPP) propagation it is possible to recreate the same near-field imaging effects as with Pendry's perfect lens. We show that a metallic meander structure is perfectly suited as such a resonant surface due to the tunability of the short (SRSPP) and long range surface plasmon (LRSPP) frequencies by means of geometrical variation. Furthermore, the Fano-type pass band between the SRSPP and LRSPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Coupled waveguide grating structure is another compelling approach to generate FRs . Knowing that the grating structure exhibits waveguide resonance, Christ et al.…”
Section: Fr Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Coupled waveguide grating structure is another compelling approach to generate FRs . Knowing that the grating structure exhibits waveguide resonance, Christ et al.…”
Section: Fr Generationmentioning
confidence: 99%
“…Coupled waveguide grating structure is another compelling approach to generate FRs [174][175][176][177][178][179][180]. Knowing that the grating structure exhibits waveguide resonance, Christ et al [181] investigated the coupling between localized particle plasmons and optical waveguide modes, which leads to the appearance of a Fano signature in transmission spectra.…”
Section: Gratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that with certain meander geometries, plasmon resonances induce a hightransmission pass band, which is bounded by two Fano-type resonances ( Fig. 2(a)) [21,29]. This high-transmission pass band is the main reason for using meander structures for the proposed depolarizer.…”
Section: Properties Of Meander Structuresmentioning
confidence: 99%
“…In the near field, systems with 1 and 2 gratings have been well analyzed since they produce Talbot and Moiré effects, respectively [6,2]. Nevertheless, there exist optical devices which use three and even more diffraction gratings in stack as, for example, optical encoders [7][8][9][10], or other applications [11][12][13]. Besides, optical devices in which the beam passes through the same grating several times can also be found [14].…”
Section: Introductionmentioning
confidence: 99%